1994
DOI: 10.1007/bf00348228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-dopant concentrations and excitation conditions on the 2 ?m fluorescence dynamics in Tm, Ho:YLF crystals

Abstract: Abstract.Results of spectroscopic studies carried out on Tm, H o : Y L F crystals are reported. In particular, we have investigated the effects of the co-dopant concentrations on the time evolution of the fluorescence at 2 gm emitted in response to short-pulse laser excitation at 792 nm. The fluorescence intensity profiles are analyzed in terms of their temporal and amplitude characteristics over a wide range of excitation conditions. PACS: 42.70Laser action at approximately 2 p.m involving 517--,5I s transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The laser thermal effect leads to the generation of an acoustic wave that changes the medium density followed by a variation of refractive index. Based on previous reports,27–29 this process is slow and can be observed in the case of CW radiation, long laser pulses, or in the case of high pulse repetition rate when heat accumulation starts to play an important role. Considering the high repetition rate of the laser we used (80 MHz), thermal lensing can also happen in our experiment, which works as a negative lens, causing the incident beam to defocus and resulting in significant energy blockage by the system aperture (finite detector size).…”
Section: Methodsmentioning
confidence: 86%
“…The laser thermal effect leads to the generation of an acoustic wave that changes the medium density followed by a variation of refractive index. Based on previous reports,27–29 this process is slow and can be observed in the case of CW radiation, long laser pulses, or in the case of high pulse repetition rate when heat accumulation starts to play an important role. Considering the high repetition rate of the laser we used (80 MHz), thermal lensing can also happen in our experiment, which works as a negative lens, causing the incident beam to defocus and resulting in significant energy blockage by the system aperture (finite detector size).…”
Section: Methodsmentioning
confidence: 86%
“…One such technique involves a combination of the single‐beam Z‐scan technique with the thermal lens technique, in which a mechanical chopper is introduced to control the exposure time of the sample by means of a default chopping frequency and a chopper opening rise time . This approach was first applied, using high‐repetition‐rate (76 MHz) femtosecond laser pulses, to separate and evaluate the pure optical third‐order nonlinearity from thermo‐optical nonlinearities in CS 2 . It was shown that cumulative effects take place in CS 2 under these excitation conditions, and result in a sign change of the nonlinear refractive index.…”
Section: Direct Methodsmentioning
confidence: 99%
“…Over the past 25 years a number of other variations of the Z‐scan technique have been introduced that extend its applicability and increase its sensitivity. These variations include the two‐color Z‐scan for measuring nondegenerate optical nonlinearities, the white‐light‐continuum Z‐scan (WLC Z‐scan), the eclipsing Z‐scan (EZ‐scan), the reflection Z‐scan (RZ‐scan), the thermally managed Z‐scan (TM Z‐scan), the generalized Z‐scan, and the intensity scan technique (I‐scan) …”
Section: Direct Methodsmentioning
confidence: 99%
“…The r −6 dependence of normalΠM1M2ED strongly suppresses long‐range contributions. Analysis of the fluorescence spectrum shows that, when the concentrations of Ho 3+ and Tm 3+ ion are restricted within relatively low doping levels (for example, 0.3% Ho 3+ , 2%Tm 3+ ‐doped YLF crystal [ 85 ] ), the energy‐transfer upconversion processes mentioned above could be suppressed and the Ho 3+ 5 I 7 → Tm 3+ 3 F 4 energy‐transfer process dominates.…”
Section: Rare‐earth Doped Solidsmentioning
confidence: 99%